Disparities in cervical cancer screening programs in Cameroon: a scoping review of facilitators and barriers to implementation and uptake of screening - Namanou Ines Emma Woks; Musi Merveille Anwi; Taal Bernard Kefiye; Dohbit Julius Sama; Angel Phuti (BMC, 2023)
Abstract Background Cervical cancer is the fourth most common cancer worldwide. Organized screening has achieved significant reductions in cervical cancer incidence and mortality in many high-income countries (HICs). But the gap between HICs and low-and-middle-income countries (LMICs) is still substantial as the highest burden of the disease is in LMICs. Cameroon is a LMIC, where cervical cancer is the leading cause of cancer-related deaths among women, only 3-5% of eligible women have been screened and there is no effective national cervical cancer prevention program. Objective(s) Identify facilitators and barriers to the implementation and uptake of existing cervical cancer screening programs in Cameroon to inform the implementation of a comprehensive national program. Methods We conducted a scoping review using the Preferred Reporting Items for Systematic Reviews and Meta-analysis, extension for Scoping Reviews (PRISMA-ScR). Google Scholar and five electronic databases (PubMed, CINAHL, Embase, Cochrane library and Web of Science) were searched systematically from 2012 to 2022. Articles on cervical cancer screening programs in Cameroon were eligible for inclusion. Two reviewers independently screened search results and extracted relevant data. Results A total of 182 articles were identified using our search strategy, and 20 were included. There was scarcity of publications from the North, Adamawa, East and South regions of Cameroon. Barriers and facilitators found were presented using the World Health Organisation framework for health systems. Cross-cutting barriers were: (1) the lack of a national training curriculum for screening providers with no elaborate, harmonized screening and treatment algorithm for cervical precancers; and (2) women's lack of information about cervical cancer screening activities. Conversely, provision of screening services at a low or no cost to women in some programs and the feasibility of using novel point of care screening methods like the Human Papillomavirus DNA test were identified as facilitators. Conclusion This scoping review indicates that there are knowledge and research gaps concerning the state of cervical cancer screening services in some regions of Cameroon. Moreover, it underlines the need for comprehensive cancer control policies and practices integrating all six-health system building blocks to reduce disparities between regions, and rural versus urban areas in Cameroon.